Subjective Well-Being in Gay - Rahmasari, Hidayatul; Rejeki, Asri (Psikostudia : Jurnal Psikologi, 2023)
Gays as discrimination in Indonesia also need subjective well-being and they have difficulty in fulfilling their subjective well-being. Researchers aim to conduct research to determine subjective well being in gays. The development of the times is also the way we think about a phenomenon that occurs in the environment around us One of them is the right of everyone to choose and have a life partner, but sometimes it is also inseparable from deviations that are currently increasingly occurring and increasingly becoming things that are starting to be accepted and taken for granted by some people, one of which is having a same-sex / homosexual partner. The research method used is qualitative research conducted with a phenomenological approach, with data mining techniques through on-on-one interview type interviews and questions arranged based on three components that can describe subjective well being, namely life satisfaction, happiness, and high welfare (Diener, 2009). In this study, the subject search was carried out Snowball Sampling technique by setting the criteria for the research subject as follows: a same-sex enthusiast or LGBT or Gay, still in a relationship or having a same-sex partner until now, and willing to willingly become a research subject. The subjects numbered 4 People. The results of research that have been conducted show the results that there are six things that describe subjective well-being in gays, namely life satisfaction, self-esteem, life experiences, romantic relationships with partners, family, and religion. The results of interviews on all four subjects also showed that all four subjects had high levels of subjective well-being.Kaum gay sebagai kaum yang deskriminasi di Indonesia juga membutuhkan subjective well-being dan mereka memiliki kesulitan dalam memenuhi kesejahteraan subjektif yang ada dalam dirinya. Peneliti bertujuan melakukan penelitian untuk untuk mengetahui Subjective well being pada Gay. Semakin berkembangnya zaman semakin berkembang pula cara berfikir kita terhadap suatu fenomenal yang terjadi dilingkungan sekitar kita Salah satunya ialah hak setiap orang untuk memilih dan memiliki pasangan hidupnya, namun terkadang juga hal tersebut tidak lepas dari penyimpangan yang saat ini semakin banyak terjadi dan semakin menjadi hal yang mulai diterima dan dianggap biasa oleh sebagian orang salah satunya yakni memiliki pasangan sesama jenis/homoseksual. Metode penelitian yang digunakan adalah Penelitian kualitatif dilakukan dengan pendekatan fenomenologi, dengan teknik penggalian data melalui wawancara tipe on-on-one interview dan pertanyaan yang disusun berdasarkan tiga komponen yang dapat menggambarkan subjective well being, yaitu kepuasan hidup, kebahagiaan dan kesejahteraan yang tinggi (Diener, 2009). dalam penelitian ini pencarian subjek dilakukan teknik Snowball Sampling dengan menetapkan kriteria subjek penelitian sebagai berikut: seorang penyuka sesama jenis atau LGBT atau Gay, masih menjalin hubungan atau memiliki pasangan sesama jenis hingga sekarang, dan bersedia dengan rela hati menjadi subjek penelitian.Subjek berjumlah 4 Orang. Hasil penelitian yang telah dilakukan menunjukkan hasil bahwa terdapat enam hal yang menggambarkan subjective well-being pada gay yaitu kepuasan hidup, harga diri, pengalaman hidup, hubungan romantis dengan pasangan, keluarga, dan agama. Hasil wawancara pada keempat subjek juga menunjukkan bahwa keempat subjek memiliki tingkat subjective well-being yang tinggi.